Increasing the Yield of Soluble Recombinant Protein Expressed in E. coli by Induction during Late Log Phase. (March 2003) - Galloway, Chad A.; Sowden, Mark P.; Smith, Harold C.
Recombinant mammalian proteins expressed in E. coli can be difficult to purify in high yield in a soluble and functional form. Various techniques have been described to prevent proteolysis of expressed proteins and/or their sequestering as insoluble aggregates within inclusion bodies. We report conditions for expressing recombinant proteins from E. coli that significantly enhanced the yield of soluble and functional protein. We demonstrate high-yield recovery of a native, high-molecular-weight RNA binding protein without the aid of fusion protein sequence. The principle factor that increased protein yield was the induction of protein expression in a late log phase culture, although reduced temperature during the induction and a low IPTG concentration also contributed to a higher yield.